Illicit Cigarette Trade in Indonesia: Trends and Analysis from the Recent Judgments - I Gede Widhiana Suarda; Evan Hamman; Bayu Dwi Anggono; Fendi Setyawan; Moch. Marsa Taufiqurohman; Zaki Priambudi (Faculty of Law, Sriwijaya University, Indonesia, 2024)
The illicit cigarette trade has begun to receive scholarly attention globally. Empirical studies on the illicit cigarette trade are available in the context of Indonesia. However, the Indonesian judicial system lacks a focus on treating illegal practices. To fill the gap, we examine Indonesian court decisions involving the illicit cigarette trade between 2010 and 2019. We provide an overview of the enforcement of Indonesiaâ€™s Excise Law 2007 relating to offences related to the illicit cigarette trade. By using a systematic quantitative literature review, we collected data on Indonesian court decisions and found the following: (1) convictions for the practice of illicit trade in cigarettes were relatively steady, with a total number from one to six court decisions annually; (2) certain offences from Indonesia Excise Law 2007 have not been found in the convictions, suggesting their underutilisation in terms of monitoring and enforcement effort; (3) the primary motivation of illicit cigarette traders as reported through the judicial system is the economic benefit or â€œprofitâ€ available to the enterprise; and (4) the sentencing decisions are dominated by the application of the â€œcumulative principleâ€ with fines and imprisonment applied at the same time. The finding on the average length of imprisonment for illicit cigarettes, which was around 18 months, shows that this crime has low risk compared with the punishment for illicit trade in drugs and narcotics in Indonesia.